Mathematical relationships of patterns of 35 rat haemodynamic parameters for conditions of hypertension resulting from decreased nitric oxide bioavailability. Issue 2 (9th January 2020) - Kurakova, Lucia; Misak, Anton; Tomasova, Lenka; Cacanyiova, Sona; Berenyiova, Andrea; Ondriasova, Elena; Balis, Peter; Grman, Marian; Ondrias, Karol
Abstract : New Findings: What is the central question of this study? Can the cross‐relationship between 35 rat arterial pulse waveform (APW) parameters be described by known mathematical functions and can mathematical parameters be obtained for conditions in a model of hypertension resulting from decreased NO bioavailability? What is the main finding and its importance? Mathematical functions and their parameters were obtained that approximate the cross‐relationships of 35 APW parameters to systolic blood pressure and to the augmentation index in conditions of decreased NO bioavailability. The results enable APW parameters to be assigned to decreased NO bioavailability, which may have predictive or diagnostic value. Abstract: Information obtained from the arterial pulse waveform (APW) using haemodynamic parameters (HPs) is useful for characterization of the cardiovascular system in particular (patho)physiological conditions. Our goal was to find out whether the relationships between rat HPs could be described by simple mathematical functions and to find mathematical parameters for conditions of high blood pressure (BP) resulting from decreased NO bioavailability. The right jugular vein of anaesthetized Wistar rats was cannulated for i.v. administration of N ω ‐nitro‐l ‐arginine methyl ester (l ‐NAME). The left common carotid artery was cannulated to detect the APW. From 10 points on the rat APW we defined 35 HPs (some were known already) and found 595 cross‐relationships between HPs showing unique patterns for particular cardiovascular conditions. Here we show parallel time‐dependent changes of 35 HPs and some of their cross‐relationships in condition of high BP induced by l ‐NAME. We found that most of the time‐dependent changes of 35 HPs and their relationships were very well fitted by simple mathematical functions, e.g. a linear function, exponential growth, exponential decay or exponential rise to maximum. The results may enable the mathematical functions to be assigned for decreased NO bioavailability, which may have predictive or diagnostic value for conditions of high BP. Using this approach, it may be possible to find unique cross‐relationship patterns of HPs and mathematical functions between HPs for different cardiovascular (patho)physiological or drug‐modulating conditions. This knowledge can be used in studying the molecular mechanisms of particular (patho)physiological conditions or drug actions and may have predictive or diagnostic value. Abstract :